Hand hygiene practices among healthcare workers - An audit conducted in a tertiary care hospital in the central province of Sri Lanka - I. K. Jayasinghe; U. A. W. L. Perera; S. R. Manilgama; N. M. Hettiarachchi; U. K. Abeywickrama; U. H. J. P. Dayaratna; B. G. Premaratne; W. G. M. D. Amarasinghe; W. L. R. Kularatne; R. S. H. T. Rotuwegama (Sri Lanka College of Internal Medicine, 2022)
Background: Proper hand hygiene (HH) is of utmost importance in reducing the prevalence of healthcare associated infections. The World Health Organisation (WHO) HH strategy has been shown to be the most effective approach leading to practice improvements. An audit was conducted to assess the adherence to HH recommendations amongst the healthcare workers (HCW) at a medical unit in National Hospital Kandy (NHK) in July 2021.   Methods: Audit standards were set to WHO five-moments HH. Four medical personnel were trained using WHO HH audit tool and asked to discreetly observe up to four HCW to assess HH over 20-minute sessions. HH compliance in total (TC), each moment and each HCW category were calculated in percentages and compared. HH compliance of 100% is the gold standard.   Results: Total of 1134 opportunities were observed. TC was 49%. Moments specific compliance were, before touching a patient (moment1): 51%, before an aseptic procedure (moment2): 67.4%, after body fluid exposure risk (moment 3): 65.2%, after touching a patient (moment 4): 69.2% and after touching patient's surrounding (moment 5): 26.7%. HCW specific compliance of doctors, nurses, healthcare assistants (HCA), medical students, allied healthcare workers (AHC), and nursing students were 54%, 49.6%, 44.8%, 4.7%, 37.1% and 11.7% respectively. Doctors were significantly more likely to be compliant overall (in all moments), and specifically in moment 4 and moment 5 HH.   Conclusions and recommendations: Overall HH compliance among HCW was inadequate at the observed study setting. Doctors demonstrated a better HH compliance than other healthcare categories. HH compliance was better in moment 4 and moment 2 than other moments. After reinforcement of HH practices, a re-audit is recommended to assess the improvement.